Emerging communication technologies for E-health and medicine - Rodrigues, Joel 1972- (Premier reference source, 2012)
"This book is a fundamental source for the advancement of knowledge, application, and practice in the interdisciplinary areas of healthcare, e-health, m-health, u-health, sensors, biomedical engineering, and telemedicine" - Provided by publisher